ARTIFICIAL INTELLIGENCE DISRUPTION: THE SHIFT OF SACREDNESS IN SEXUAL RELATIONS - Nunung Sanusi; Sandra Irawati; Havid Lazuardi; Vercia Muhamad Ali Umar (PT Altin Riset Publishing, 2026)
The development of artificial intelligence (AI)-based sex dolls has shifted the paradigm of human sexual relations toward increasing artificiality. Sex dolls are no longer merely erotic objects but have become sexual simulacra, replacing the human presence as subjects in relationships. This study employs Jean Baudrillard’s theories of simulation, simulacra, and hyperreality to analyze how sex dolls reconstruct sexual experience while degrading the sacred and existential dimensions of sexuality. Using a qualitative analytical approach, this research explores how sex dolls disrupt sacredness within sexual relations. The analysis reveals that sex dolls create a form of sexual hyperreality in which sex is no longer rooted in the biological body and emotional relationships, but rather in images, fantasies, and unilateral mechanistic control. This indicates that the use of sex dolls has the potential to disrupt the spiritual and emotional meaning of sexual relations. Such changes reflect a shift in values; from sexual relationships traditionally bound by norms, morality, and spiritual symbolism toward functional relations and the personalization of artificial intimacy.